High oxygen sensitivity of TiO2 thin films deposited by ALD - Almaev, Aleksei V.; Yakovlev, Nikita N.; Almaev, Dmitry A.; Verkholetov, Maksim G.; Rudakov, Grigory A.; Litvinova, Kristina I. (Micromachines)
The gas sensitivity and structural properties of TiO2 thin films deposited by plasma-enhanced atomic layer deposition (ALD) were examined in detail. The TiO2 thin films are deposited using Tetrakis(dimethylamido)titanium(IV) and oxygen plasma at 300 °C on SiO2 substrates followed by annealing at temperatures of 800 °C. Gas sensitivity under exposure to O2 within the temperature range from 30 °C to 700 °C was studied. The ALD-deposited TiO2 thin films demonstrated high responses to O2 in the dynamic range from 0.1 to 100 vol. % and low concentrations of H2, NO2. The ALD deposition allowed the enhancement of sensitivity of TiO2 thin films to gases. The greatest response of TiO2 thin films to O2 was observed at a temperature of 500 °C and was 41.5 arb. un. under exposure to 10 vol. % of O2. The responses of TiO2 thin films to 0.1 vol. % of H2 and 7 × 10–4 vol. % of NO2 at a temperature of 500 °C were 10.49 arb. un. and 10.79 arb. un., correspondingly. The resistance of the films increased due to the chemisorption of oxygen molecules on their surface that decreased the thickness of the conduction channel between the metal contacts. It was suggested that there are two types of adsorption centers on the TiO2 thin films surface: oxygen is chemisorbed in the form of O2– on the first one and O– on the second one.